ISO 9000 implementation guidelines - Blignaut, Vincent (My University, 2016)
This project compares the ISO 9000 series with the Deming-based total quality management philosophy. The series are also equated with the Deming prize and the Malcolm Baldrlge National Quality Award as a trilogy in achieving total quality management. Many companies which have implemented total quality management are requiring their suppliers to meet quality standards to assure a consistent product or service. The SABS ISO 9000 series is presently a prevalent method of assessment of suppliers. Concerns that ISO registration would be the only way LV ensure sales to the European Community have partially diminished, while pressure from domestic firms have increased. especially for companies facing competitive bidding from supplier contracts This driving force may result in companies not reaping the advantages of total quality management, as their quality systems are simply designed to meet ISO 9000 requirements, Analysis, primary and secondary research identified weaknesses and strengths of the ISO standards and Awards. Suggestions are made to those companies in the process ofISO registration in moving to a total quality environment.
A research project submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1995.
Keywords: Total quality management--South Africa.; Quality control--South Africa.